Neonatal and pediatric intensive care in Rio de Janeiro State, Brazil: an analysis of bed distribution, 1997 and 2007 Terapia intensiva neonatal e pediátrica no Rio de Janeiro, Brasil: distribuição de leitos e análise comparativa de equidade em 1997 e 2007 - Arnaldo Prata Barbosa; Antônio José Ledo Alves da Cunha (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study was to describe the characteristics of neonatal and pediatric intensive care units (ICU) and beds in Rio de Janeiro, correlating with population demands in 1997 and 2007. All neonatal and pediatric ICUs were visited, identifying the availability and type of beds. Comparisons were made between: supply and demand using projected need for beds for the population; public and private ICUs; and geographical regions. In 2007, 95 units were included totaling 1,094 beds (74 units and 1,080 beds in 1997): 51% public and 48% private (47% and 52% in 1997); 47% neonatal, 18% pediatric and 35% mixed units. Most units were located in the metropolitan area. The distribution of public and private beds was similar in the metropolitan area in both periods; in the interior, public beds tripled. Access has improved, mainly in the interior, but there is still no equity in the distribution of and accessibility to the available beds, with a shortage in the public sector, an excess in the private sector, and a great concentration in the metropolitan area. Descrever as características das unidades de terapia intensiva (UTI) neonatais e pediátricas e leitos no Rio de Janeiro, Brasil, correlacionando com demandas da população em 1997 e 2007. UTIs neonatais e pediátricas foram visitadas, identificando-se o tipo e disponibilidade de leitos. Foram feitas comparações entre: a oferta e a demanda projetada da necessidade de leitos para a população, a natureza pública ou privada das UTIs e regiões geográficas. Em 2007, 95 unidades foram incluídas, totalizando 1.094 leitos (74 e 1.080 leitos em 1997): 51% públicas e 48% privadas (47% e 52% em 1997); 47% neonatais, 18% pediátricas e 35% mistas. A maioria estava localizada na região metropolitana. A distribuição dos leitos públicos e privados foi semelhante na região metropolitana em ambos os períodos, no interior os públicos triplicaram. O acesso melhorou, principalmente no interior, mas ainda não há equidade na distribuição e no acesso aos leitos disponíveis, com falta no setor público, excesso no privado, e grande concentração na região metropolitana.